(untitled) (American Journal of Islam and Society, 2015)
This paper argues that the transdisciplinary approach, contrary to the views of some of its advocates, is not a methodology but a metamethod. In the first part I shall briefly discuss the similarities and differences between science/knowledge and technology to explain important epistemic implications of placing this approach in the latter category. Next, I shall critically examine the views of Basarab Nicolescu, one of the most prolific proponents of a particular reading of this approach. Part three discusses the function of the transdisciplinary approach as a meta-method. In the fourth and final part I shall try to introduce some examples from the intellectual econiche of Islamic culture in a bid to shed further light on this approach’s potential as a meta-method. The conclusion, which I draw from my own critical examination, is that the transdisciplinary approach can be used in an effective way, provided that its users adopt an appropriate philosophical framework. Such a framework, I contend, could be provided by critical rationalism.